Tips and tricks of basic navigation in forest area / Wan Noni Afida Ab Manan, Shahida Hanum Kamarullah and Nur Sha’adah Zainuddin - Ab Manan, Wan Noni Afida; Kamarullah, Shahida Hanum; Zainuddin, Nur Sha’adah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In many incident scenarios, being able to navigate with a map and compass is crucial. Map and compass skills are still necessary even with modern technology, such as Global Positioning System (GPS) receivers. Practise and expertise in navigation skills lead to confidence. This confidence level frequently affects how an individual performs in a crisis, which may need making life or death decisions. Although it occasionally happens, becoming lost is not the goal of navigation; rather, it involves tracking your position as you travel away from a known location. You must keep an eye on the landscape you are leaving behind, the territory you are passing, and the terrain in front of you as you travel. Knowing your starting location, destination, and path in the wilderness is essential for navigation. With these abilities, you'll be able to travel further than you ever imagined off the usual route. You will need to use known human pathways, ridge lines, streams, dry riverbeds, or wildlife paths because the jungle and many rainforests are so dense. This is acceptable if your intended path of travel is traveling in the same direction, but this isn't the case most of the time. The inability to move in straight lines makes navigation more challenging.